1970
DOI: 10.1029/rs005i003p00605
|View full text |Cite
|
Sign up to set email alerts
|

On VLF Radiation Resistance of an Electric Dipole in a Cold Magnetoplasma

Abstract: By using full‐wave theory, an analysis is made of the radiation resistance of a short filamentary electric dipole, oriented with an arbitrary angle with respect to the static magnetic field, in a cold, uniform magnetoplasma. The frequency range considered lies below the local lower hybrid resonance frequency and above the proton gyrofrequency, and in this range approximate closed‐form expressions for the radiation resistance are obtained by using a plasma model appropriate to the magnetosphere. These closed‐fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

1973
1973
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 2 publications
1
40
0
Order By: Relevance
“… Kulkarni et al [2006] expanded on the results presented in Inan et al [2003] to determine source locations in L ‐shell and geomagnetic latitude, operating frequencies and initial wave normal angles needed to fill the inner radiation belts with whistler‐mode wave energy. The authors used the Stanford VLF raytracing code [ Inan and Bell , 1977], coupled with path‐integrated Landau damping and a realistic model [ Wang and Bell , 1970] of dipole antenna radiation in a magnetoplasma. Kulkarni et al [2006] considered both equatorial and off‐equatorial source locations, and concluded that three transmitters radiating in accordance with the Wang and Bell [1970] antenna model are sufficient to fill the inner magnetosphere with whistler‐mode wave energy, although the authors ignored longitudinal spreading of the rays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Kulkarni et al [2006] expanded on the results presented in Inan et al [2003] to determine source locations in L ‐shell and geomagnetic latitude, operating frequencies and initial wave normal angles needed to fill the inner radiation belts with whistler‐mode wave energy. The authors used the Stanford VLF raytracing code [ Inan and Bell , 1977], coupled with path‐integrated Landau damping and a realistic model [ Wang and Bell , 1970] of dipole antenna radiation in a magnetoplasma. Kulkarni et al [2006] considered both equatorial and off‐equatorial source locations, and concluded that three transmitters radiating in accordance with the Wang and Bell [1970] antenna model are sufficient to fill the inner magnetosphere with whistler‐mode wave energy, although the authors ignored longitudinal spreading of the rays.…”
Section: Introductionmentioning
confidence: 99%
“…The authors used the Stanford VLF raytracing code [ Inan and Bell , 1977], coupled with path‐integrated Landau damping and a realistic model [ Wang and Bell , 1970] of dipole antenna radiation in a magnetoplasma. Kulkarni et al [2006] considered both equatorial and off‐equatorial source locations, and concluded that three transmitters radiating in accordance with the Wang and Bell [1970] antenna model are sufficient to fill the inner magnetosphere with whistler‐mode wave energy, although the authors ignored longitudinal spreading of the rays.…”
Section: Introductionmentioning
confidence: 99%
“…This slow decay rate distinguishes the generation of the whistler waves by magnetic dipole and the RMF source antennas from the generation of whistler waves by an electric dipole antenna, which has been studied by many authors theoretically, experimentally, and numerically. [12][13][14][15][16][17][18] In Ref. 14 it is clearly demonstrated that in the case of linear small magnitude whistler waves driven by the electric dipole antenna the magnitude of the wave decays very fast along the ambient magnetic field even in the collisionless plasma due to the fact that the energy radiated is nearly evenly distributed inside the resonance cone.…”
Section: Comparison Of Emhd Model and Experimentsmentioning
confidence: 99%
“…Previous authors have characterized the radiation reactance in the far-field region of an electric dipole immersed in a magnetoplasma and in the absence of a plasma sheath [3], [16], [17], [18]. More specifically, Balmain [3] develops a quasi-static approximation of the far-field radiation resistance that is valid for any orientation of the electric dipole with respect to the magnetic field.…”
Section: Introductionmentioning
confidence: 99%